EASE OF USE AND TRUST IN PURCHASING DECISIONS ON THE SHOPEE APPLICATION - Lailatul Rohmah; Zainal Fanani (International Journal of Economics, Science, and Education, 2024)
This study aims to describe the analysis of the effect of ease of use, security, and trust on purchasing decisions on the shopee application on STIE Youth Surabaya Students. The data analysis technique used is a quantitative method using the SPSS program version 25.0. This study used descriptive statistical analysis and multiple linear regression. The sample in this study was as many as 100 respondents. The results of this study show that Ease of Use, Security and Trust simultaneously have a positive and significant effect on Purchasing Decisions using the Shopee application for STIE Youth Surabaya students, where F counts at 22.746 while F table is 3.09 and significant 0.000 < 0.05. The results of the R2 test show that an Adjusted R Square of 0.397 means that purchasing decisions can be obtained and explained by the variables of ease of use, security and trust.